Análisis financiero en el comercial Alexa supermercado de la ciudad de Macará. Periodos 2020-2021. - Factos Tandazo, Karla Lizbeth (2022)
The following research work entitled FINANCIAL ANALYSIS IN THE COMMERCIAL "ALEXA SUPERMARKET" OF THE CITY OF MACARÁ. DURING 2020 - 2021, was carried out as a prerequisite in order to obtain the degree of Engineer in Accounting and Auditing, Public Accountant-Auditor CPA, at the National University of Loja, thus conforming to the academic regulations in force. The analysis of the financial statements of the Company was developed based on the fulfillment of the proposed objectives. On the other hand, for the elaboration of the work both in its theoretical and practical part is based on the application of different methods, starting from the scientific method that allowed the classification of concepts based on proven theories; followed by the deductive and inductive method with which the information collected was ordered from the general to the more specific; the mathematical method to perform operations; the statistical method that facilitated the consolidation of data in tables and graphs that allow a more efficient appreciation of the results and finally the analytical and synthetic method used to define policies, conclusions and recommendations that allow the correct decision making. Additionally, in order to fulfill the first specific objective, a vertical and horizontal analysis was performed, calculating the variations of each of the groups and items that make up the economic and financial structure, of which, the most relevant within the assets are the current assets with a weight of 99.99% in 2020 and 93.52% in 2021, this includes the inventories that the commercial company has for sale, within the liabilities the one that had the highest participation was the current liabilities with 61.60% in 2020; meanwhile, for 2021, current liabilities had 10.63% due to the decrease in other current obligations and customer advances; as for its economic structure, the income from ordinary activities in the account of net sales of premises are the ones with more contribution, being 101% in 2020 and 100.41% in 2021, which represent a great income, therefore, an increasement in profits; This was done in order to gather information on the financial situation of the business and its economic and financial status, and then a review of the financial statements performed to perform the vertical and horizontal analysis of the years 2020 - 2021, in order to know the composition of assets, liabilities and equity, in relation to the changes that occurred from one year to another. Likewise, the financial indicators of liquidity, activity, profitability and 5 indebtedness were applied to evaluate the economic and financial position of the company, being this information of great relevance for the analysis of its liquidity and profitability. As a conclusion to this proposal, it ends with the presentation of the financial analysis report, which summarizes the results obtained to the owner of the company, providing comments, conclusions and recommendations for making correct and timely decisions to improve the financial management of the ALEXA SUPERMARKET.